Early open bite treatment: What is important to know? (Research, Society and Development, 2021)
The aim of this study was to evaluate the main treatment methods for anterior, dentoalveolar or skeletal open bites, taking into account the advantages and complications involved during these treatment phases for the stabilization of the bite of children during their craniofacial development phase. The studies selected to compose the literature review published in the last 10 years in the following databases in the health area: PubMed/Medline, Scopus, LILACS, SciELO and Cocrhane. The main results showed that the main objective of early treatment of anterior open bite is the elimination of harmful oral habits, making use of various devices and devices that were primarily effective in reducing negative overbite, improving the positioning of the tongue and teeth, in addition to skeletal physiological changes. This allows us to conclude that the methods used for the early treatment of anterior open bite are very effective in increasing overbite and providing physiological functions for the stomatognathic system with long-term stability of these alterations.